Kebugaran jasmani di SMPN Se-Kecamatan Candi Kabupaten Sidoarjo - Huda, Moch Miftachul; Wahyudi, Usman; Darmawan, Arief (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2022)
Fitness is an important aspect of daily activities. Having good physical fitness can help students better in carrying out their daily activities. This study aims to determine the level of physical fitness of SMPN students in Candi District. This type of research is quantitative descriptive. The method used is a survey using the Nusantara Student Fitness Test (TKPN) instrument. The number of samples in this study were 100 students based on the calculation of the slovin formula by dividing the sample in each school using proportion calculations according to the population in each school. The results of this study indicate that the physical fitness of class VII students at SMPN Se Kecamatan Candi in the very good category is 0 students, in the good category are 0 students, in the moderate category are 38 students, in the low category are 62 students, and in the very low category as many as 0 students.